An analysis of UK firms' disclosures about derivatives usage in their corporate reports. (4th August 2010) - Dunne, Theresa; Helliar, Christine; Power, David
This paper examines the different factors that may influence the quantity of firms' disclosures about derivatives usage. The analysis focuses on the disclosures that were mandated by Financial Reporting Standard (FRS) 13 and examines these for a sample of UK firms' corporate reports. The study focuses on three reasons why companies disclose information: to maintain their reputation (reputation); to avoid proprietary costs of disclosure (proprietary); and to provide information that will give a more complete picture of the financial well-being of the organisation (financial). The study focuses on disclosures about derivatives information in total as well as for currency risk, interest rate risk and liquidity risk. The analysis is also broken down for Financial Times Stock Exchange (FTSE) 100 companies, other listed companies and Alternative Investment Market (AIM) companies. The findings show that reputational and financial factors seem to be the most important reasons as to why companies tend to disclose more FRS 13 information; the proprietary costs argument is not well supported.